Serunya Pembelajaran IPAS dengan Talking Stick: Upaya Peningkatan Proses dan Hasil Belajar Siswa Kelas IV - Rohmah, Shofi Ainur; Sundahry, Sundahry; Agrita, Tri Wera (Master of Pedagogy and Elementary School Learning, 2025)
Classroom Action Research (CAR) is motivated by initial observations showing that the learning process has not optimized the use of learning models, with students tending to be less enthusiastic in participating in the IPAS learning, resulting in low IPAS learning outcomes in grade IV at SDN 94/II Muara Bungo. In order to improve students' learning outcomes in each cycle, the Talking Stick learning model is applied in the IPAS subject. The research method used is CAR. The research is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The subjects of this research are the 29 students of grade IV at SD Negeri 94/II Muara Bungo. The data collection techniques include observation, tests, and documentation, with data collection instruments using observation sheets for educators and students, as well as test questions, and then analyzed through qualitative and quantitative data analysis techniques. The research results show the process and learning outcomes of IPAS in the 4 grade of SDN 94/II Muara Bungo. The details of the teacher's observation results in cycle I achieved a percentage of 85.50% in the good category, and in cycle II achieved a percentage of 92.50% in the very good category. The results of the student observations in cycle I achieved a percentage of 68.96% in the sufficient category, and in cycle II achieved a percentage of 87.93% in the good category. The learning outcomes of the students in cycle I achieved a percentage of 72.41% with the very good/good criteria, and in cycle II achieved a percentage of 86.21% with the very good/good criteria. It can be concluded that the use of the Talking Stick model can improve the process and learning outcomes of IPAS.